2021 IEEE International Conference on Communications Workshops (ICC Workshops) 2021
DOI: 10.1109/iccworkshops50388.2021.9473627
|View full text |Cite
|
Sign up to set email alerts
|

Air-to-Ground Directional Channel Sounder With Drone and 64-antenna Dual-polarized Cylindrical Array

Abstract: Unmanned Aerial Vehicles (UAVs), popularly called drones, are an important part of future wireless communications, either as user equipment that needs communication with a ground station, or as base station in a 3D network. For both the analysis of the "useful" links, and for investigation of possible interference to other ground-based nodes, an understanding of the air-to-ground channel is required. Since ground-based nodes often are equipped with antenna arrays, the channel investigations need to account for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…At present, many approaches have been adopted, For example, the noise threshold in [38] was 25 dB lower than the CIR's strongest path power. In [39], it was 20 dB higher than the mean power of the noise level. In [40], it was 20% of the CIR's strongest path power.…”
Section: Channel Knowledge Extractionmentioning
confidence: 82%
See 1 more Smart Citation
“…At present, many approaches have been adopted, For example, the noise threshold in [38] was 25 dB lower than the CIR's strongest path power. In [39], it was 20 dB higher than the mean power of the noise level. In [40], it was 20% of the CIR's strongest path power.…”
Section: Channel Knowledge Extractionmentioning
confidence: 82%
“…We use the CIR obtained from the actual measurement for comparison and verification. Figure 4 shows that the adaptive noise threshold generated by the ML-CFRA method at P CFAR = 10 −0.42 , W = 36 and N G = 2 is compared with the constant noise threshold in [38,39]. It can be seen that the use of a constant noise threshold may lead to some multipaths with low power not being missed, resulting in measurement errors.…”
Section: Channel Knowledge Extractionmentioning
confidence: 99%
“…Following [6], the authors in [25] studied the Doppler effect at millimeter-wave (mmWave) frequencies for an air-to-ground channel under random UAV wobbling. Apart from analytical results, measurement campaigns have also reported the impact of wobbling as an important source of error in establishing a strong connection in aerial wireless networks [26], [27]. In particular, in [26], the authors used a channel sounder to investigate an air-to-ground wireless link, from which they observed that the variations of the received power from a completely static UAV are much less than that of a hovering UAV.…”
Section: A Related Workmentioning
confidence: 99%
“…Apart from analytical results, measurement campaigns have also reported the impact of wobbling as an important source of error in establishing a strong connection in aerial wireless networks [26], [27]. In particular, in [26], the authors used a channel sounder to investigate an air-to-ground wireless link, from which they observed that the variations of the received power from a completely static UAV are much less than that of a hovering UAV. These studies highlight the importance of considering UAV wobbling in aerial wireless communications.…”
Section: A Related Workmentioning
confidence: 99%